Zakat houses design and planning (quality and standard) from shariah perspective - Aripin, Srazali; Abdul Rashid, Khairuddin; Ahmad Sarkawi, Azila; Hasan, Sharina Farihah; Mohd Fauzi, Puteri Nur Farah Naadia (Malaysian Institute of Planners., 2019)
The paper focusses on the provision of shelter or housing for asnaf fakr and miskin by zakat administrators in Malaysia. The objectives of the study are to ascertain whether the design and planning (quality & standard) of zakat housing (1) satisfies the need and well-being of the households (i.e. the asnafs) in terms of appropriateness and adequacy, (2) meets the requirement of shariah (aesthetic, privacy, space requirements, facilities and amenities) and (3) could potential arrive at the key success factors for zakat houses from shariah perspectives. The study was carried out through desktop analysis of the literature review of zakat, housing for asnafs and house design for shariah added with semi-structured interview of the occupants living in zakat houses. Key findings from the study are the zakat houses occupied by the asnafs are neither appropriate nor adequate in terms of meeting the needs and requirements of the households of the asnafs. Limited literature is found describing the specifications of zakat houses or the state and conditions of such houses and houses repaired or rented. The study recommends that zakat administrator should consider establishing their own and shariah compliant standards for zakat funded housing for the asnafs.